Iodine Catalyzed Ozone Destruction at the Texas Coast and Gulf of Mexico. Issue 15 (3rd August 2018) - Tuite, K.; Brockway, N.; Colosimo, S. F.; Grossmann, K.; Tsai, C.; Flynn, J.; Alvarez, S.; Erickson, M.; Yarwood, G.; Nopmongcol, U.; Stutz, J.
Abstract: Iodine monoxide and ozone measurements were taken using long‐path differential optical absorption spectroscopy along the Gulf of Mexico coast near Galveston, Texas, in spring/summer of 2016. During the eight‐week campaign, half of the days were characterized by O3 between 12 and 25 ppb. These air masses coincided with onshore flow and had measurable levels of IO, with an average daily maximum around 0.8 ppt and values as high as 2 ppt. The presence of IO indicates the influence of iodine chemistry which catalytically destroys O3 . Using observed IO and NO2 levels, along with model HO2 data, an O3 destruction rate between 1.5 and 2 ppb/day was calculated. Assuming a background O3 level of 30 ppb, it is very likely that iodine chemistry is responsible for destroying enough O3 along a 10‐day back trajectory through the Gulf of Mexico to explain the low mixing ratios frequently experienced along the Texas coast. Plain Language Summary: In order to efficiently plan ozone mitigation strategies and improve air quality in urban regions, it is important to understand all possible sources and sinks of ozone. Air quality models, however, have difficulty capturing the low ozone levels in marine air that blows onshore, indicating that an important chemical mechanism may be missing in coastal regions. Reactive iodine species, which are emitted from the ocean, are known to destroy ozone and may be responsible for this unaccounted ozone loss. Here we present measurements of iodine monoxide (IO) from a field site along the Gulf of Mexico coast in Texas, 80 km southeast of Houston. The levels of IO detected during periods of onshore flow, along with supporting modeling data, indicate that reactive iodine plays a significant role in ozone destruction as air masses travel over the Gulf of Mexico and into Texas. These findings can help improve local air quality models in Texas to better determine ozone compliance within Houston and the state. Key Points: Iodine monoxide was measured during periods of low ozone along the Gulf of Mexico coast in Texas Observed iodine monoxide levels indicate that ozone destruction rates of up to 2 ppb per day are possible Iodine catalyzed ozone destruction likely explains the low ozone levels along the Texas coast during onshore flow events